2021
DOI: 10.1111/ejn.15557
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in behaviour, mood and functional capacity in the primary progressive aphasia variants

Abstract: Primary progressive aphasia (PPA) is a neurodegenerative clinical syndrome characterised by a progressive decline in speech and language functions. Deficits in behaviour, mood and functional capacity are reported in PPA but are less well understood. This study examined the PPA variants' profiles on these domains at initial presentation and over time and evaluated their relations to overall cognitive ability. Behaviour, mood and functional capacity were measured annually (over $6 years) in 145 individuals diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…These individuals progressed over time to straddle the AD and FTLD syndrome spaces. PPA patients further went on to accumulate functional and affective deficits with time, 71 and the accrual of functional and motor impairments predicted their survival status at 3 years post-baseline. 72 In the context of ongoing debates, the current findings concur with a growing literature in PPA supporting the emergence of non-linguistic and functional changes which (i) are sometimes notable in early stages of the disease, when assessed appropriately; 73–75 (ii) are present systematically in most variants, irrespective of the type and severity of their language disorder; 30,32,76 and (iii) may not directly relate to specific pathological substrates.…”
Section: Discussionmentioning
confidence: 99%
“…These individuals progressed over time to straddle the AD and FTLD syndrome spaces. PPA patients further went on to accumulate functional and affective deficits with time, 71 and the accrual of functional and motor impairments predicted their survival status at 3 years post-baseline. 72 In the context of ongoing debates, the current findings concur with a growing literature in PPA supporting the emergence of non-linguistic and functional changes which (i) are sometimes notable in early stages of the disease, when assessed appropriately; 73–75 (ii) are present systematically in most variants, irrespective of the type and severity of their language disorder; 30,32,76 and (iii) may not directly relate to specific pathological substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, while PNFA is described as primarily a language disorder with relative sparing of behavioral abnormalities [ 5 ], several studies have reported the emergence of behavioral changes as early as 1-year post-baseline assessment affecting empathy [ 49 ]. Others have also reported increased behavioral and emotional disturbances in this group 6 years after baseline assessment [ 49 51 ]. Given that behavioral abnormalities are primarily linked with damage to neuroanatomical structures in the right hemisphere, it is plausible that global amygdala volume loss, notably the pronounced decline in the right hemisphere, underlies the emergence of emotional and behavioral disturbances observed in PNFA patients.…”
Section: Discussionmentioning
confidence: 66%
“…Patients initially present to the clinic complaining of a “loss of memory for words” (Hodges & Patterson, 2007), however, formal neuropsychological testing indicates a progressive loss of conceptual knowledge. Importantly, this degradation of conceptual knowledge is pan‐modal, occurring irrespective of modality, while other cognitive functions such as attention, executive function, and visuospatial function, remain relatively intact until much later in the disease course (Foxe, Irish, Hu, et al, 2021; Foxe, Irish, Ramanan, et al, 2021). The neuroanatomical signature of SD follows a well‐defined pathway, commencing in the anterior temporal lobe, most severe on the ventral surface, and encompassing the anterior fusiform and perirhinal cortices (Mion et al, 2010; Figure 5).…”
Section: Semantic Dementiamentioning
confidence: 99%